Ichthyofaunal diversity in the lower Narayani River, Chitwan, Nepal - Shah, Deep Narayan; Tachamo-Shah, Ram Devi; Sharma, Subodh; Maharjan, Junu; Sada, Rajesh (Nepal Journal of Environmental Science, 2022)
Narayani River in Nepal is an excellent habitat for diverse groups of aquatic organisms. A stretch of 70 km of lower Narayani River was studied for fish diversity and composition. A total species richness of 40 representing 14 families and 7 orders was reported. Order cypriniformes had high taxa dominance of 67% whereas least taxa richness of only 2 % with single species were recorded from orders Beloniformes, Clupeiforms, Gobiiformes and Osteoglossiformes. Simpson diversity index ranged from 0.1 to 0.8 whereas Shannon diversity and Pielou’s evenness ranged from 0.2 to 2.1 and 0.3 to 0.8, respectively. Minimum taxa richness and abundance were recorded in river stretches with industrial effluents situated along the bank of the river. High conservation species such as Wallago attu, Chitala chitala, Tor tor and Neolissochilus hexagonolepis were documented in the most downstream section, i.e., Tribeni of the river. Non-metric multidimensional scaling (NMDS) analysis distinguished three clusters of sites for the river where fish community composition was found to be significantly different (p <0.05). The outcomes of the study help identifying critical river stretches that need high conservation efforts for conserving fish diversity in the lower Narayani River.